Literature Review: The Characteristics Of Central Nervous System Tumors - Nurhikmah; Achmad Harun Muchsin; Aziz Beru Gani (International Medical Journal Corp. Ltd, 2025)
Brain tumors are one of the tumors that have poor progression and can develop into malignancies depending on the location of the tumor. Central nervous system (CNS) tumors include primary tumors and metastatic tumors located in the brain and spinal cord..This research method was conducted with a literature review through the collection of various research journals and obtained 10 samples of related research literature. The results showed that the characteristics of central nervous system tumors were predominantly male, aged ≥18 years, the most common type of primary SPP tumor was glioblastoma, the most common location of lesions was supratentorial and based on the most common complaints were headaches.